Effects of sunshades on temperature and cow comfort - Shirley, John E. (Kansas Agricultural Experiment Station, 2011)
Sunshades provide an effective method of reducing ultraviolet sunrays and increasing cow comfort.
Keywords: Sunshades; Environmental temperature; Cow comfort